Formulation Of Effervescent Tablet Of Temulawak Extract (Curcuma xanthorrhiza Roxb.) With Variation Of Stevia As Sweetener - Cessa Lynatra; Wardiyah Wardiyah; Yetri Elisya (Politeknik Kesehatan Kemenkes Jakarta II, 2018)
The effervescent tablet containing extract of temulawak (Curcuma xanthorrhiza Roxb.) with variation of stevia sweetener has been formulated using wet granulation method. This research aims to find the formulation of effervescent tablet of temulawak extract (Curcuma xanthorrhiza Roxb.) with the variation of stevia sweetener that meets the requirements of physical tablet test. The effervescent tablet formula was made in three formulas with the difference in the stevia content. Tests conducted include visual tests, uniformity test, hardness test, friability test, pH test and solubility test. Based on the test results on the physical properties of tablets, it is known that all the formula meets the physical test of tablets and the preferred formula is formula 3 with 4% of stevia.